Retrospeksi Ekonomi-Politik Kebijakan Pemberantasan Kemiskinan di Pedesaan - Hamel, Victor A (Magister Administrasi Publik (MAP) FISIPOL Universitas Gadjah Mada, 1999)
Using a political-economy model of analysis introduced by Uphoff and Ilchman (1972), the writer tries to analyze the